A brief review of multicultural counselling self-efficacy and multicultural counselling competency - Harun, Maizatul Mardiana; Abdul Kadir, Rusnani; Mohd Noah, Sidek (IDOSI Publications, 2014)
The globalisation process which has taken place all over the world has not only changed the horizon but greatly impacted human race, especially human culture and tradition. The impact on the society can be clearly seen by the reality in the school. School as the miniature of today’s society challenged the teachers with various severe issues by the students. Most of these issues such as random sex, homosexuality, suicide and bullying are very much related to the student’s background. Thus, counselling teachers need to exhibit multicultural counselling competency and be confident when serving multicultural clients. The multicultural counselling competency has long been promoted since 1982 is said to consist of three components namely belief and attitude, knowledge and skills related to multicultural counselling. One of the ways to assess one’s competency is by measuring the multicultural counselling self-efficacy and multicultural counselling competency. Therefore, the purpose of this review is to explore the concepts of multicultural counselling self-efficacy and multicultural counselling competency especially from the perspective of Social Cognitive Theory (SCT).